A(maize)ing attraction: gravid Anopheles arabiensis are attracted and oviposit in response to maize pollen odours. (December 2017) - Wondwosen, Betelehem; Hill, Sharon; Birgersson, Göran; Seyoum, Emiru; Tekie, Habte; Ignell, Rickard
Abstract Background Maize cultivation contributes to the prevalence of malaria mosquitoes and exacerbates malaria transmission in sub-Saharan Africa. The pollen from maize serves as an important larval food source forAnopheles mosquitoes, and females that are able to detect breeding sites where maize pollen is abundant may provide their offspring with selective advantages.Anopheles mosquitoes are hypothesized to locate, discriminate among, and select such sites using olfactory cues, and that synthetic volatile blends can mimic these olfactory-guided behaviours. Methods Two-port olfactometer and two-choice oviposition assays were used to assess the attraction and oviposition preference of gravidAnopheles arabiensis to the headspace of the pollen from two maize cultivars (BH-660 and ZM-521). Bioactive compounds were identified using combined gas chromatography and electroantennographic detection from the headspace of the cultivar found to be most attractive (BH-660). Synthetic blends of the volatile compounds were then assessed for attraction and oviposition preference of gravidAn. arabiensis, as above. Results Here the collected headspace volatiles from the pollen of two maize cultivars was shown to differentially attract and stimulate oviposition in gravidAn. arabiensis . Furthermore, a five-component synthetic maize pollen odour blend was identified, which elicited the full oviposition behavioural repertoire of the gravid mosquitoes. Conclusions The cues identified from maize pollen provide important substrates for the development of novel control measures that modulate gravid female behaviour. Such measures are irrespective of indoor or outdoor feeding and resting patterns, thus providing a much-needed addition to the arsenal of tools that currently target indoor biting mosquitoes.